Targeted Anti-HER2 Cancer Therapy in Elderly Women Diagnosed with Breast Cancer - Molina-Garrido, M.J.; Guillen-Ponce, C.; Mora-Rufete, A. (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Trastuzumab or lapatinib treatment with chemotherapy or hormonotherapy are the gold standard treatments for human epidermal growth factor receptor 2 (HER2)-positive breast cancer (early breast cancer or metastatic breast cancer). Older patients have been largely underrepresented in clinical trials, and few data on trastuzumab or lapatinib efficacy and toxicity have been reported for this subgroup. This article has reviewed the main articles that have analyzed these items.
Keywords: histology